Civil rights, policy diffusion and the coevolution of immigration and public health in the American food system - Welsh, Edward S., author; Velasco, Marcela, advisor; Duffy, Robert, advisor; Orsi, Jared, committee member (Colorado State University. Libraries, 2021)
This research uses the 'policy diffusion framework' to analyze the mechanisms and motivations behind policymaking in the American food system and draw conclusions about the relationship between the policy process and civil rights. It also utilizes analytical concepts lent by historic institutionalism such as process tracing and critical junctures to create a narrative of policy evolution from a cross-case analysis of the most salient issues facing the food system including immigration and public health policies. A case study of the northern Colorado food system details a series of policy adoptions in these issue areas, offering metrics for measuring equality. I hypothesize that the policy diffusion process in the real world has a causal relationship with the civil rights of immigrants and migrants working in food service. I ask the research question, what is the relationship between the policymaking process and civil rights in the food system, and what mechanisms of policy diffusion are active? I find that the policy diffusion process has the best outcomes for civil equality when there is a diversity of stakeholders who take a collaborative approach to the process and share information quickly and often. But, when decisionmakers bias the process by excluding or favoring sets of stakeholders, then the information flow is crippled and policy outcomes negatively affect civil rights.
Keywords: food desert; immigration; policy diffusion; historical institutionalism; COVID-19; meatpacking